2000
DOI: 10.1109/10.828149
|View full text |Cite
|
Sign up to set email alerts
|

Vectorcardiographic loop alignment and the measurement of morphologic beat-to-beat variability in noisy signals

Abstract: The measurement of subtle morphologic beat-to-beat variability in the electrocardiogram (ECG)/vectorcardiogram (VCG) is complicated by the presence of noise which is caused by, e.g., respiration and muscular activity. A method was recently presented which reduces the influence of such noise by performing spatial and temporal alignment of VCG loops. The alignment is performed in terms of scaling, rotation and time synchronization of the loops. Using an ECG simulation model based on propagation of action potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 10 publications
0
35
0
1
Order By: Relevance
“…Thereby, the VCG analysis results may be affected. However, in 1998 and 2000, the articles published by Sörnmo [81] and Astrom et al [5] developed the method for reducing the affect of respiration and muscular activity on VCG loops in a beat-to-beat manner. Mainly, they reduced the respiration influence by performing spatial and temporal maximum-likelihood (ML) alignment of the VCG loops, and this alignment was based on scaling, rotation, and time synchronization of the loops.…”
Section: Respirationmentioning
confidence: 98%
“…Thereby, the VCG analysis results may be affected. However, in 1998 and 2000, the articles published by Sörnmo [81] and Astrom et al [5] developed the method for reducing the affect of respiration and muscular activity on VCG loops in a beat-to-beat manner. Mainly, they reduced the respiration influence by performing spatial and temporal maximum-likelihood (ML) alignment of the VCG loops, and this alignment was based on scaling, rotation, and time synchronization of the loops.…”
Section: Respirationmentioning
confidence: 98%
“…Åström et al [23]studied the QRS Loop Morphology and itsrelationship with the established noise level. By using a measure related to loop planarity, it was demonstrated that the alignment breakdown noise level had an essentially linear dependence on loop planarity.…”
Section: Discussionmentioning
confidence: 99%
“…The above algorithm will converge to a steady solution. For simplicity, we denote the above algorithm containing expressions (2), (6), and (7) by OrigALG.…”
Section: Principle Of Bss Algorithm Based On Hosmentioning
confidence: 99%